Evaluation of Anticonvulsant Activity of Kochia Scoparia L. Schrad (Amaranthaceae) Volatile Oil (Nigerian Journal of Pharmaceutical Research, 2021)
Background: Epilepsy is one of the most common serious neurological disorders.  Most antiepileptic or anticonvulsant drugs do not prevent or reverse the pathological process that underlies epilepsy, hence the continuous search for new therapeutic agents with minimal side effects and greater efficacy.Objective: The objectives of this study were to determine the acute toxicity profile and investigate the anticonvulsant activity of volatile oil of Kochia scoparia (Amaranthaceae ).Method: Volatile oil was extracted from fresh leaves of K. scoparia through hydrodistillation process, using a Clavenger-type apparatus. Acute toxicity testing was done using Lorke’s method. The anticonvulsant models used were pentylenetetrazol, strychnine and maximal electroshock.  Albino mice were randomly divided into five groups (n=5). Group I (control group) was given 0.2 ml each of water orally while groups II, III and IV received 75, 150 and 300 mg/kg of the volatile oil. Group V received the standard drug solution; 30 mg/kg phenobarbitone for Maximal electroshock and 2 mg/kg diazepam for pentylenetetrazol and strychnine models. The onset of tonic leg extension, duration and protection from mortality were noted. Results:  Sub acute toxicity test revealed that doses above 1000mg/kg of the volatile oil is toxic. Doses of 75, 150 and 300 mg/kg significantly (P 0.05.Conclusion: The volatile oil of K. scoparia could be useful in the management of epilepsy.